2019
DOI: 10.3390/ijerph16030333
|View full text |Cite
|
Sign up to set email alerts
|

The Factors Affecting Older Adults’ Intention toward Ongoing Participation in Virtual Reality Leisure Activities

Abstract: Due to the aging of organs, older adults may have limited physical strength for participating in outdoor activities. Therefore, indoor activities offer an alternative for maintaining the health of older adults. Following advances in technology, individuals can use virtual reality to exercise in their homes and are no longer subject to the constraints of the outdoor environment or weather conditions. In addition, these activities are easier to participate in when compared to real-world leisure activities. The p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 40 publications
(54 reference statements)
0
9
0
1
Order By: Relevance
“…Previously published articles on PA in VR focus on the possibility of its implementation in public health activities. Many publications emphasize the potential of this form of movement, recognizing it as a modern trend in healthcare [37,38], mainly in the field of secondary prevention [18,34,35]. There are also reports regarding the assessment of gait parameters in a virtual environment [39,40].…”
Section: Introductionmentioning
confidence: 99%
“…Previously published articles on PA in VR focus on the possibility of its implementation in public health activities. Many publications emphasize the potential of this form of movement, recognizing it as a modern trend in healthcare [37,38], mainly in the field of secondary prevention [18,34,35]. There are also reports regarding the assessment of gait parameters in a virtual environment [39,40].…”
Section: Introductionmentioning
confidence: 99%
“…Physical activity in combination with serious video games is a feasible and effective strategy to improve the upper and lower body, flexibility, balance and agility in older adults. As in [42], our main contribution is the insertion of new technologies but in Mexican adult environments, with cultural and customized activities, may boost the engagement with exercise; however we contribute further by also provide to additional health information to therapists or medical doctors and engaging the older adult with moderate activity, activity that impacts directly in their well-being.…”
Section: Discussionmentioning
confidence: 99%
“…dos Santos Mendes et al (2012) Virtual Reality "A computer-based technology providing a multisensorial environment with which the user can interact." Yeh et al (2019) VR "a computer-generated reality that allows users to enter a virtual world through a computer interface" cybersickness with older adults with schizophrenia (Chan et al, 2010), another indicated that most of their PTSD patients reported no negative effects after exposure to a virtual environment displayed in an HMD. Despite this, research still maintains that older adults are a high-risk group for cybersickness (Matas et al, 2015).…”
Section: Article Definitionmentioning
confidence: 99%